Implementasi Teknologi Informasi Enterprise Resource Planning (ERP) Studi Pada Perusahaan Kemasan - Eko Purwanto; Prasetyohadi Prasetyohadi; Firman Dwilaksono Rahardianto (Jurnal Manajemen dan Bisnis Indonesia, 2014)
The purpose of this research is to test the influences of critical success factors of ERP implementation. The use of variables based on the results of previous research, which directly influences the Top management support, Business Process Reengineering, Effective Project Management and Education and training toward critical success factors of ERP Implementation. The use of these variables can solve the problems in determining appropriate strategies for the successful ERP Implementation. According to Martin (1998) 90% of ERP implementation has been delayed and the success rate is only about 33%. The population used in this research were all ERP users at a packaging company and the sample size is 57 people. Data collection techniques in this research using questionnaires and data analysis technique using Partial Least Square (PLS) which is run with the help of Smart PLS 2.0 M3 software. The analysis showed that Top Management Support and Education and training influence the success of ERP implementation, while the other variables such as Business Process Reengineering and Effective Project Management does not affect the successful implementation of ERP. To increase the success rate of ERP implementation, users on the companies that are or have implemented ERP systems should consider some factors such as Top Management Support and Education and training because these factors shown to affect the success rate of ERP implementation. Keywords : ERP, Implementation, Information Technology and PLS.